Review of PPCPs remediation in Asia: The role of agricultural waste in adsorption-membrane hybrid technology - Ntone, Ellora Priscille Ndia; Rozaimi, Abu Samah; Mohamad Syafiq, Abdul Wahab; Alsalhy, Qusay Fadhil; Sunarti, Abd Rahman (Taylor & Francis, 2025)
The escalating prevalence of emerging contaminants, notably pharmaceutical and personal care products (PPCPs), poses a significant threat to global freshwater reservoirs, environmental equilibrium, and human well-being. Trace amounts of these micropollutants persist within aquatic environments, posing challenges in their detection, analysis, and wastewater remediation using conventional approaches. Enhanced tertiary treatments (ETTs), encompassing methods such as adsorption on activated carbon (AAC), advanced oxidation processes (AOP), and membrane separation process (MSP), have been introduced to address these challenges. This review underscores the pressing necessity for economical and efficacious alternatives, with a particular focus on polymeric membrane technology for membrane-based wastewater treatment. The polymeric membrane approach demonstrates cost-effectiveness, facile production, and excellent pollutant selectivity. Furthermore, the paper explores the viability of utilizing agricultural waste as an alternative adsorbent material within adsorption-membrane hybrid systems. Introducing an innovative approach—adsorption-membrane hybrid technology utilizing agricultural waste—this review advances beyond existing literature. By leveraging polymeric membrane technology alongside the unique attributes of agricultural waste adsorbents, this strategy aims to enhance the efficacy of wastewater treatment. Noteworthy for its comprehensive exploration of adsorbent precursors derived from agricultural waste, this review presents a novel and promising avenue for wastewater treatment advancement.